Suicide Leap of an 11-Year-Old Girl with Autism Spectrum Disorder - Yuki Takahashi MD; Katsunaka Mikami MD, PhD; Fumiaki Akama MD, PhD; Yuichi Onishi MD; Kenji Yamamoto MD, PhD; Hideo Matsumoto MD, PhD (SAGE Publishing, 2020)
Autism Spectrum Disorder (ASD) has been linked with risk of suicide, and several cases of suicide attempts by adolescents with ASD have been reported. However, there is scant research on therapeutic approaches to prevent suicide re-attempts by children with ASD who have already attempted suicide. We report our experience of treating an 11-year-old girl with adjustment disorder comorbid with ASD who was transported to our hospital after sustaining injuries from the suicide leap. Initially, she was diagnosed with adjustment disorder brought on by poor interpersonal relationships at school, and, upon reviewing the patient's personal history, her underlying ASD characteristics became apparent. To prevent a re-attempt, it was crucial to reduce her risk factors and enhance her protective factors. To reduce her risk factors, we manipulated the environmental factor that triggered the patient's suicide attempt. In addition, to reinforce her protective factors, we intervened in the parent-child relationship and addressed her hesitation to ask for help, which we identified as a predisposing factor since early childhood. Over the course of her treatment, she did not exhibit suicidal ideation or re-attempt suicide.